INCIDENCIA DEL BONO JOAQUÍN GALLEGOS LARA EN LA DIMENSIÓN BIENESTAR MATERIAL REFERIDA A LA CALIDAD DE VIDA DE LOS BENEFICIARIOS DEL CANTÓN PIÑAS, PERÍODO 2018 - Maldonado Huailas, Edwin Alexander (2020)
The present investigation entitled “Incidence of the Joaquín Gallegos Lara bond in the material dimension referred to the quality of life of the beneficiaries of the Piñas canton, Period, 2018”, was executed according to what is established by the regulations of the National University of Loja, as a requirement prior to obtaining the title of Engineer in Public Administration. The main purpose of this research is to determine the impact of the Joaquín Gallegos Lara Bond on the quality of life of people in a state of vulnerability, specifically in the material dimension. To achieve this purpose, the Piñas canton of the province of El Oro was taken as empirical evidence, where quantitative and qualitative analysis tools were applied. The importance of this study lies in the possibility of objectively analyzing the changes in the material conditions of people with disabilities who receive this benefit granted by the Ecuadorian state in order to offer data and results academically structured to analyze the impact of this type of programs. In general, this research aims to determine the impact of the Joaquín Gallegos Lara program on the material well-being of people with severe and profound disabilities. Specifically, the objectives of the present work are: to describe the social characteristics of the beneficiaries, to identify the material conditions that people had before receiving this benefit and the modification that has occurred after being beneficiaries of this program. The material dimension has been considered as part of this study because it is part of the elements that are part of people's quality of life. 5 The methodology applied corresponds to quantitative and qualitative tools that were processed to analyze the social conditions of the beneficiaries. The sources from which the information was obtained were the institutional channels responsible for this program. This information contributed to the recognition of the new levels of material well-being of people, with this information and in comparison with the responses of the first part of the survey, the variation propitiated by the governmental economic transfer could be established. The results obtained from the application of these tools with the support of the information obtained in the literature review, allowed us to determine that the level of incidence of the Joaquín Gallegos Lara bond in the material dimension of people with severe and profound disabilities was 28 , 73% in relation to the income indicator, it was also possible to visualize an incidence of 14.74% in the possessions indicator and a 13.82% incidence in the housing indicator. These conditions allow to determine that the monetary transfer policies destined by the State to improve the quality of life of the people, give effective results in material aspects associated with the acquisition of resources used by these people.